UNA LECCION SOBRE PLEURESIAS TUBERCULOSAS - BANDALA, OCTAVIO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1949)
Observations were made on the hydremia, plasma chlorides, fluid loss by sweating and temp and respiratory rate changes of normal or febril monkeys tied in a supine position on a padded board in ordinary (Ca 23[degree]C) or hot (40[degree]C) environment
REV MEX TUBERCULOSIS
Keywords: LECCION, PLEURESIAS, TUBERCULOSAS; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA